Boosting the Antimicrobial Activity of Quaternary Ammonium Photosensitizers by Janus‐Type AIE Luminogens - Dongyang Fan; Meng Li; Zipeng Shen; Ying Li; Jingjing Guo; Dong Wang; Ting Han; Ben Zhong Tang (Aggregate)
ABSTRACT Cationic compounds with quaternary ammonium structures are one of the most commonly utilized antibacterial materials, which can effectively overcome the emergence of bacterial drug resistance. Systematic investigation on the structure‐activity relationship of such cationic compounds is essential for the development of efficient antimicrobials toward different bacterial strains with clear antimicrobial mechanisms. In this study, we rationally designed and synthesized two quaternary ammonium photosensitizers with aggregation‐induced emission (AIE) properties. One possesses a unilaterally charged and Janus‐type structure with two positively charged moieties at one tail and two hydrophobic alkyl chains on the other side. The other is a bilaterally symmetric molecule bearing quaternary ammonium structures at both ends. The fluorescence staining experiments, bactericidal assays, and bacterial morphology analyses reveal that the Janus‐type AIE luminogen show superior photodynamic antimicrobial activities possibly due to its better disruption of the bacterial membranes. Further theoretical study on the molecule‐membrane interaction and molecular dynamics gains deeper insights into the intrinsic relationships between molecular structures and antibacterial activities, which provides a feasible design strategy for high‐performance antimicrobial agents.